Main principles and approaches on the Ingushetia republic biodiversity preservation - T. U. Tochiev; A. M. Batkhiev; M. K. Dakieva (Юг России: экология, развитие)
The paper considers the basic principles and approaches of the maintenance, developing and preservation of Ingushetia biodiversity, which is presented by lots of ecological-fauna and fauna-genetic groups of ancient genetic fund. It has many features presenting a big practical and theoretical interest.